The exile in poetry: readings by Guta (As três Marias) and Edna (Riacho Doce) - Gaiotto de Moraes, Ricardo; da Silva Vieira, Viviane (Faculdade de Educação/Universidade Estadual de Campinas, 2020)
Published in 1939, As Três Marias, by Rachel de Queiroz, and Riacho Doce, by José Lins do Rego, have in common women protagonists, whose trajectories are marked by different school experiences, but, at the same time, by an intense coexistence with written literature (novels, poems ) and oral literature (narratives and popular songs). Punctuating the differences of record, because in "As Três Marias" Guta's memories are recorded in first person and in "Riacho Doce" Edna's trajectory is narrated in third person, this article seeks to study how the literary formations of the characters mark their expectations regarding the future and provoke reflections about the limits imposed on women in the society in which the narratives are inscribed.